Law Enforcement of Money Politics in Regional Head General Elections - Muslim, Mohammad Buchori (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
The number of cases of violations that occurred in the implementation of regional head general elections, for example money politics. A number of parties with an interest in certain candidates provide money or other objects to voters or organizers. Against this background, this research was conducted to find out and discuss the accountability of the perpetrators of money politics in regional head elections and the legal consequences imposed on perpetrators of money politics violations in regional head elections as stipulated in Law Number 10 of 2016 concerning the Second Amendment to the Law Law Number 1 of 2015 concerning the Stipulation of Government Regulations in lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors to Become Laws. For research methods using normative juridical research methods that are qualitative. From the research, it is known that one of the factors causing the practice of money politics is the weak regulations on money politics in regional head elections and weak enforcement of penalties. Even though the law has expressly prohibited the practice of money politics, it still happens a lot. so in addition to improving the existing regulations in the legislation, it is also necessary to strengthen the role of related institutions and community participation.